The Potential of Active Compounds from Melinjo Leaves (Gnetum gnemon) as an Antihistamine using Molecular Docking Approach for Acetylcholine Muscarinic M3 Receptor Inhibition - Gaspersz, Nelson; Amos, Matthew Adi Honey; Male, Yusthinus T.; Baharudin, Muh. Daswar A.; Leuwol, Dean Y.E.; El, Rahma; Pattiasina, Priska M.; Sohilait, Mario R.; Herland Satriawan (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Melinjo leaves (Gnetum gnemon) have been used traditionally in Maluku to treat spoilage in the fish product. Melinjo leaves contain secondary metabolites with anti-inflammatory and antibacterial biological activities. It has been identified contain gnetumal, callyspinol, cassipuorol, (+)-dehydrovomifoliol, p-coumaric acid, ferulic acid, isovitexin, swersitin, isoswersitin, vicenin 2, swertiajaponin, isoswertiajaponin and ursolic acid. This research aims to predict the potential of the compounds in melinjo leaves as antihistamines by inhibiting the activity of the acetylcholine muscarinic M3 receptor. The research was carried out using an in silico study method using a molecular docking approach. Docking results showed that gnetumal, callyspinol, cassipuorol, (+)-dehydrovomifoliol, p-coumaric acid, ferulic acid, isovitexin, swersitin, isoswersitin, vicenin 2, swertiajaponin, isoswertiajaponin and ursolic acid for the muscarinic acetylcholine receptor M3 had a binding affinity value of -7.4, -8.0, 7.0, 7.0, -6.6, -6.6, -7.4, -5.7, -4.4, -3.7, -6.0, -4.9 and -4.7 kcal/mol, respectively.